2012
DOI: 10.1111/apt.12123
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trials: linaclotide phase 3 studies in IBS‐C – a prespecified further analysis based on European Medicines Agency‐specified endpoints

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 33 publications
7
107
0
2
Order By: Relevance
“…Linaclotide was shown to be well tolerated and efficacious for the treatment of patients with IBS-C in 2 randomized, double-blind, placebocontrolled studies, as well as additional post-hoc analyses (Table 1) [Castro et al 2013;Chey et al 2012;Macdougall et al 2013;Quigley et al 2013;Rao et al 2012Rao et al , 2014. In one randomized, controlled study, a significantly greater percentage of Abdominal pain responder defined as patient with improvement from baseline ⩾30% in mean weekly worst abdominal pain score or mean weekly abdominal discomfort score for…”
Section: Targeting Gi Motilitymentioning
confidence: 99%
“…Linaclotide was shown to be well tolerated and efficacious for the treatment of patients with IBS-C in 2 randomized, double-blind, placebocontrolled studies, as well as additional post-hoc analyses (Table 1) [Castro et al 2013;Chey et al 2012;Macdougall et al 2013;Quigley et al 2013;Rao et al 2012Rao et al , 2014. In one randomized, controlled study, a significantly greater percentage of Abdominal pain responder defined as patient with improvement from baseline ⩾30% in mean weekly worst abdominal pain score or mean weekly abdominal discomfort score for…”
Section: Targeting Gi Motilitymentioning
confidence: 99%
“…16 Several large-scale clinical trials supported the use of linaclotide in treating IBS-C, demonstrating the ability of the compound to improve colonic transit, improve abdominal pain and ameliorate pathologic bowel habits when compared to placebo. [41][42][43][44][45][46][47] Moreover, linaclotide's side effect profile was favorable, with the most common adverse event being diarrhea (in approximately 20% of patients), perhaps not surprising given GUCY2C's role in traveler's diarrhea. Other less common events included abdominal pain and distention, flatulence, gastroenteritis and headache.…”
Section: Clinical Translation Of Gucy2c Ligands For Colorectal Cancermentioning
confidence: 99%
“…Interestingly, the correlation between aggregate measures of published studies addressing bowel patterns and pain correspond with results of a pilot study, which demonstrated a significant relationship between changes in bowel frequency and pain ratings for individual patients receiving linaclotide for constipation. 62 The described correlation between improved pain ratings were not only reported in studies of the newly introduced agents for IBS-C, [63][64][65][66][67] but were also observed in many other trials, which did not meet inclusion criteria for this analysis and examined the effects of interventions ranging from fiber supplements, 68,69 to herbal preparations, 70 biofeedback, 71 bisacodyl, 72 or osmotic laxatives. [73][74][75] While not the focus of this analysis, we noted some statistically significant, but clinically minor, differences in the endpoints between patient cohorts with constipation and IBS-C.…”
Section: Discussionmentioning
confidence: 71%